Understanding the in vitro neuromuscular activity of snake venom Lys49 phospholipase A(2) homologues - Gallacci, Marcia [UNESP]; Cavalcante, W. L. G. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Phospholipases A(2) (PLA(2)s) with a lysine substituting for the highly conserved aspartate 49, Lys49 PLA(2) homologues, are important myotoxic components in venoms from snakes of Viperidae family. These proteins induce conspicuous myonecrosis by a catalytically-independent mechanism. Traditionally, the Lys49 PLA(2) homologues are classified as non-neurotoxic myotoxins given their inability to cause lethality or paralytic effects when injected in vivo, even at relatively high doses. However, a series of in vitro studies has shown that several Lys49 PLA(2) homologues from Bothrops snake venoms induce neuromuscular blocking activity on nerve-muscle preparations in vitro. The interpretation of these findings has created some confusion in the literature, raising the question whether the Lys49 PLA(2) homologues present some neurotoxic activity. The present article reviews the in vitro neuromuscular effects of Lys49 PLA(2) homologues and discusses their possible mechanisms of action. It was concluded that the neuromuscular blockade induced by Lys49 PLA(2) homologues in isolated preparations is mainly a consequence of the general membrane-destabilizing effect of these toxins. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Snake venom; Phospholipase A(2); Neuromuscular junction